The Effect Leader-Member Exchange and Interpersonal Communication on Employee Job Satisfaction - Putri, Yuki Andarifta; Fathiyah, Kartika Nur (LifeSciFi, 2025)
Job satisfaction reflects an individual's enthusiasm and fulfilment in performing work tasks, making it a crucial factor in employee performance. Among the key determinants of job satisfaction are the quality of leader-member relationships and effective interpersonal communication. Leaders must align their leadership style with employees’ preferences and establish strong communication within the organization. This study aims to examine the influence of leader-member exchange and interpersonal communication on job satisfaction among employees at the Ministry of Religious Affairs Office, Sleman Regency. Using a quantitative approach with survey methods, the study involved 115 employees selected through a saturated sampling technique. The instruments used include the Interpersonal Communication Scale, the leader-member exchange, and the Job Satisfaction Scale. Validity was tested using Gregory analysis, and reliability. Data analysis using multiple linear regression with SPSS version 22 revealed that both leader-member exchange and interpersonal communication significantly affect job satisfaction. The findings suggest that higher quality relationships between leaders and subordinates, along with effective interpersonal communication, enhance employee job satisfaction.